Resolution of Refractory Status Epilepticus With Ketamine Without Intubation in a Patient With Stroke-Like Migraine Attacks After Radiation Therapy (SMART) Syndrome - Kyle N. Kaneko; Pablo Read; John M. Eaton; Yoshie Umemura; Justin L. Hoskin (Case Reports in Neurological Medicine)
Stroke-like migraine attacks after radiation therapy (SMART) syndrome is an infrequently reported complication arising years after radiation therapy that manifests as a reversible syndrome marked by migraine-like headaches, focal neurologic signs, and/or seizures. Refractory status epilepticus (RSE) associated with SMART syndrome is rare and can be challenging to treat. Valproic acid has been reported to improve seizures in RSE in SMART syndrome in a few case reports and may be ideal for SMART syndrome, given its use in the treatment of migraines and seizures. Ketamine has been used in RSE and a few instances in SMART syndrome. Here, we present a case of refractory focal status epilepticus in a patient with SMART syndrome who was treated with ketamine, which resolved seizures without the need for intubation.